Strategi Pemasaran KOPONTREN MBU Dalam Menarik Minat Menabung Pada Masyarakat Mojopurogede Bungah Gresik - Muhammad Zaidan Farih Fakhruddin Tri Budhi Adhi (SAUJANA : Jurnal Perbankan Syariah dan Ekonomi Syariah, 2024)
This research aims to examine the efforts made by Kopontren MBU in increasing community interest, particularly in the Mojopurogede village, to engage in savings. Kopontren MBU, or the Cooperative of Manbaul Ulum Islamic Boarding School, is a developing financial services company that requires initiatives to enhance customer interest in saving. Using a qualitative approach, this research involves in-depth interviews, observations, and document analysis to comprehensively understand the efforts undertaken by Kopontren MBU. The findings of this research indicate that Kopontren MBU has successfully implemented several strategies, including excellent service quality, diverse product offerings, and effective marketing strategies. Socialization efforts targeting local government institutions and educational establishments from kindergarten to high school levels were employed. Additionally, bonuses were provided to Kopontren MBU members with specific balances, known as mudharabah deposit products.